THE MOST SHALLOW OIL TRAP IN THE WORLD OF WONOCOLO ANTICLINE AS A BEAUTIFUL EDUCATION OBJECT - Setiawan, Jatmika; Kristanto, Dedy; Hariyadi, Hariyadi (Journal TECHNO, 2021)
Wonocolo is located in Bojonegoro District who one of geosite of 20 geosite point to support The Petroleum Geoheritage Bojonegoro. Wonocolo is area’s of Asset-4 Pertamina Cepu. Wonocolo area is a good interesting to develope as Geological Tourism object of old well, because in this area to exploitation of hidrocarbon with tradisional system use  car’s mechine and with rig of Jati Threes. The deep of reservoir Wonocolo only about 200-400m from survace. The many rig to explorer hidrocarbon tradisionally, so like in the Texas. So this study to make the Geological Tourism Object of Wonocolo Old Well with economy improvement of Wonocolo Community, Bojonegoro, East Java. Things that can be developed there among other: 1. Tracking get the jeep, tracking trail and tracking a bicycle, 2. Wells pilot; 3. Places beautiful to photograph a selfi, 4. The existence of transit equipped with photographs wonocolo from year to year of fossils, and Wonocolo’s maket, 5. The development of its tourism education in all quarters. This intended to give addition to entrepreneurs mining with the tourism and finally as an alternative income if later oil in wonocolo up.